Advancing Nuclear Astrophysics Using Next-Generation Facilities and Devices - C. Langer; N. Klapper; C. Köppchen; S. Dababneh; R. Reifarth (Jordan Journal of Physics, 2025)
Where are all the heavy elements formed? How are they formed? What is the role played by stars and stellar explosions? Nuclear astrophysics aims at answering these fundamental scientific questions by linking nuclear physics with astrophysical modelling and observations. Large progress has been achieved in past decades. However, new nuclear physics facilities and devices are urgently required to advance research into regions of the nuclear chart so far not reachable. This will enable unprecedented studies of nuclear reactions in the laboratories, which are key for heavy element synthesis and the fate of a star. Some highlights of upgrade-in -process will be described. Experimental effort needs to be guided by astrophysical modelling to find significant uncertainties and pinpoint important measurements to be carried out. For two astrophysical scenarios, sensitivity studies using detailed nuclear network calculations will be presented. These calculations involve charge-particle induced reactions like (p,Y) or (a,Y) during the rapid proton capture process (rp process). On the other hand, core-collapse supernovae can be studied using rare presolar type C SiC grains. Observed peculiar abundance distributions in these grains can be explained with the conditions during the nucleosynthesis. We therefore study the light mass Si-S region by variations of (n,Y) reaction rates. Also, the influence of different neutron pulses and the effect on the final abundances of the production of the important radioisotope 32Si are examined. Both investigations stress the need for enhanced experimental approaches to measure reaction rates to better constrain the astrophysical sites. Keywords: Nuclear astrophysics, Presolar grains, Nuclear physics, Facilities, Network calculations.